Patient’s opinion about tangible aspect of Universitas Padjadjaran Dental Hospital - Perkasa, Endrou Daulat; Susilawati, Sri; Gumuruh, Grace Virginia (Universitas Padjadjaran, 2014)
Introduction: Every hospital seeks to provide the best service quality in order to fulfill patient’s expectations. One of the service quality dimensions’ indicator of consumer satisfaction is tangible aspect. Tangible describes the availability of facilities and physical performance that can be directly perceived by consumers, readily defined as representation the patient’s satisfaction level of hospital service quality. The purpose of this study was to determine the patient’s opinion about tangible aspect in RSGM UNPAD. Methods: The study was conducted using a descriptive research survey method. sampling method using purposive technique sampling. Data obtained from a survey conducted by researcher from patients who had received treatment at RSGM UNPAD. A questionnaire was used as validation instrument. Results: The service elements of the appearance in non-medical employees which have an mean value of 3.036.Tangible aspect of RSGM UNPAD has total mean value of 2,684. This result include the employees’s performance, location of RSGM and some facilities available in RSGM. The results of the study in table 3 show the service elements of UNPAD RSGM facilities have an mean value of 1,985. mean value of dimension of the physical appearance dimensions of RSGM UNPAD of 2.684. Conclusion: RSGM UNPAD have good mean value in tangible aspects according to patient’s opinion.